2001
DOI: 10.1046/j.0263-4929.2001.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact metamorphic P–T–t paths from Sm–Nd garnet ages, phase equilibria modelling and thermobarometry: Garnet Ledge, south‐eastern Alaska, USA

Abstract: Sm–Nd garnet‐whole rock geochronology, phase equilibria, and thermobarometry results from Garnet Ledge, south‐eastern Alaska, provide the first precisely constrained P–T–t path for garnet zone contact metamorphism. Garnet cores from two crystals and associated whole rocks yield a four point isochron age for initial garnet growth of 89.9 ± 3.6 Ma. Garnet rims and matrix minerals from the same samples yield a five point isochron age for final garnet growth of 89 ± 1 Ma. Six size fractions of zircon from the adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 36 publications
2
28
0
2
Order By: Relevance
“…The PeT paths integrate rim thermobarometry and pseudosections following the techniques presented by Vance and Mahar (1998), Stowell et al (2001), and Stowell and Tinkham (2003). Garnet rim thermobarometry was used to estimate PeT at peak metamorphic conditions with the average PeT routine of THER-MOCALC (Powell and Holland, 1988;Powell et al, 1998) using externally calculated activities.…”
Section: Methodsmentioning
confidence: 99%
“…The PeT paths integrate rim thermobarometry and pseudosections following the techniques presented by Vance and Mahar (1998), Stowell et al (2001), and Stowell and Tinkham (2003). Garnet rim thermobarometry was used to estimate PeT at peak metamorphic conditions with the average PeT routine of THER-MOCALC (Powell and Holland, 1988;Powell et al, 1998) using externally calculated activities.…”
Section: Methodsmentioning
confidence: 99%
“…MnO, CaO and Na 2 O were included in the pseudosection calculations for compositions of garnet and plagioclase, therefore the MnNCKFMASH system should be suitable for modeling the P−T history. We used the intersection relationships among isopleths of X Mn , X Fe and X Ca in garnet compositions (e.g., Vance and Holland 1993;Vance and Mahar, 1998;Stowell et al, 2001;Kim and Bell, 2005) via the program THER-MOCALC (Powell and Holland, 1988;Powell et al, 1998) to examine the P−T path revealed by garnet cores that have grown at different stages of development relative to the succession of FIAs. Standard deviation ranges are 712°C in temperature and 0.2−0.5 kbar in pressure.…”
Section: Methodsmentioning
confidence: 99%
“…In many cases, and particularly for metapelitic rocks, either or both of these approaches is adequate (e.g. Vance & O'Nions 1990;Burton & O'Nions 1991Vance et al 1998b;Vance & Harris 1999;Stowell et al 2001;Th6ni 2002;Stowell & Tinkham 2003). However, it has been known for some time (Jagoutz 1988;Th6ni & Jagoutz 1992;Luais et al 2001;Th6ni 2002) that in (mainly coarse-grained) high pressure metabasic rocks this is often not the case.…”
Section: Advances In the Chronometry Of Major Metamorphic Minerals -Pmentioning
confidence: 99%
“…Mezger et al 1989;Christensen et al 1989Christensen et al , 1994Vance & O'Nions 1990Burton & O'Nions 1991Vance et al 1998b;Vance & Harris 1999;Stowell et al 2001;Th6ni 2002;Stowell & Tinkham 2003) but it is not robust. It is the experience of the lead author on this paper that the success rate, as measured by the ability to obtain age precisions of 1-3 Ma, is less than 50%.…”
Section: Advances In the Chronometry Of Major Metamorphic Minerals -Pmentioning
confidence: 99%
See 1 more Smart Citation